The Basic Research of Internal Combustion Engine Performance in Different Swirl Ratio - Liu, Yong Feng; Yi, Li; Shi, Yan; Jia, Xiao She (Applied Mechanics and Materials, 2014)
In order to investigate the effect of swirl intensity on the performance of the diesel engine, the 4JB1 diesel engine was taken as the research subject and KIVA-3V program was used to calculate the temperature, pressure, NOx and SOOT in cylinder and the performance of dynamic and economy of the diesel engine by changing the value of swirl ratio. The results show that increasing the swirl ratio in the cylinder can make the hybrid combustion of fuel and air sufficiently, improving the combustion temperature and pressure in the cylinder, enhanced the power of the diesel engine and reduced fuel consumption. The generation of NOx increased with the increases of swirl ratio and the production of SOOT decreased with the increases of swirl ratio.